Feedback on rowers' mechanical power output improves compliance to intended on-water training intensity - Lintmeijer, L. L.; Hofmijster, M. J.; Robbers, F. S.; Knoek van Soest, A. J.; Beek, P. J. (ISBS Proceedings Archive (Michigan), 2017)
In rowing, mechanical power output (MPO) is a defining characteristic of training intensity and may be used to control on-water training intensity. However, rowers` behavioural response to real-time feedback on MPO need to be examined first. The aim of this study was to test whether rowers are able to comply with MPO targets when they receive realtime feedback on MPO. Eighteen rowers performed training sessions in which they rowed at different intensities while receiving traditional feedback or additional real-time feedback on MPO. Rowers reduced the difference between target MPO and delivered MPO during all intensity intervals, while between-strokes fluctuations in MPO were only diminished during the medium-high intensity intervals when real-time feedback on MPO was provided. We conclude that rowers adjust their behaviour based on real-time feedback on MPO. Therefore, it has the potential to improve control of training intensity in on-water rowing.